Characteristics of adolescents requiring intensive care in the United Kingdom: A retrospective cohort study. (August 2018) - Wood, Dora; Goodwin, Sarah; Pappachan, John; Davis, Peter; Parslow, Roger; Harrison, David; Ramnarayan, Padmanabhan
Objectives: To describe the case mix, resource use and outcomes for adolescents admitted to intensive care units in the UK. Methods: Analysis of national prospectively collected data for all adolescents aged 12–19 years admitted to UK adult or paediatric intensive care units. Results: There were 37, 320 admissions of adolescents during the eight–year study period. Excluding elective surgery, respiratory diagnoses were the most common reason for paediatric intensive care unit (PICU) admission, with trauma and intoxication the most common reasons for adult intensive care unit (AICU) admission. Intensive care unit mortality was 6.0% and 5.7% for those admitted to PICUs and AICUs, respectively. Conclusions: Mortality is similar among adolescents admitted to AICUs and PICUs; however, these rates have not been corrected for severity of acute illness or underlying burden of chronic illness, which may be different between AICUs and PICUs. Services planned for the majority of AICU and PICU patients may not be optimal for critically ill adolescents treated in UK intensive care units, who may need special consideration.